Green magnetically separable molluscicide Ba–Ce–Cu ferrite/TiO2 nanocomposite for controlling terrestrial gastropods Monacha Cartusiana - Abdullah A. Alamri; Mohamed A. Ayyad; Hossameldin G. Mohamedbakr; Usama A. Soliman; Majed Y. Almashnowi; Jia Hong Pan; Elsayed T. Helmy (Scientific Reports)
Abstract The increasing economic damage caused by terrestrial gastropods, especially the Monacha cartusiana (M. cartusiana) land snail, to the agricultural sector requires a diligent and continuous search for new materials and alternatives for the control operations. In this piece of work, a magnetically separable molluscicide with high effectiveness green Barium–Cerium–Copper ferrite/TiO2 (Ba–Ce–CuFO/TiO2) nanocomposite was greenly prepared using Eichhornia plant aqueous extract and characterized using different techniques. The green Ba–Ce–CuFO/TiO2 nanocomposite was applied as an aspect of the attempts to search for new active substances that would have a potential toxic effect against M. cartusiana. Laboratory toxicity evaluations by leaf dipping and contact methods showed LC50 values of 1218.79 and 289.19 ppm, respectively. Analysis of biochemical variables as a bio response indicator showed a noticeable increase in the values of aspartate transaminase (AST) and alanine transaminase (ALT) relative to the control, while the decrease was characteristic for alkaline phosphatase (ALP) and total protein (TP) other variables when the animals were treated with LC50 value. The histopathological examination was performed on both the muscular foot and the digestive gland, or what is known as the hepatopancreas, which showed enlarged lumens and damaged digestive cells, in addition to destructed digestive tubes, the existence of pyknotic nuclei, and hematocyte infiltration. Foot histopathology showed ruptured epithelial cells, deep folds, and empty spaces when animals were treated with our target nanocomposite LC50 value. Application under natural field conditions through the bait technique showed a significant satisfactory population diminution after 14 days of exposure, as the mean percentage of diminution was 72.2% compared to the recommended pesticide Neomyl SL 20%, which poses a 74.27% reduction. Built on the above, we recommend further studies of the usage of green Ba–Ce–CuFO/TiO2 nanocomposite, and the introduction of such nanocomposite in gastropod control operations to reduce losses in the agricultural sector in general.